Determinants Of Going Concerned Audit Opinion Acceptance - Putri Meilinda; Riswan Riswan; Aminah Aminah (International Journal of Economics, Business and Innovation Research, 2024)
A going concern audit opinion is an opinion issued by the auditor that is used in order to consider the ability of a company or business to survive. This study aims to analyze the effect of profitability and company growth on the acceptance of going concern audit opinions by auditors in conducting audit assessments. Solvency variables are used as moderating variables in the study. The data used in this study are mining sector companies listed on the Indonesia Stock Exchange in 2020–2022. The sample amounted to 54 companies out of a total of 81 samples, and the sampling method was purposive sampling. The analysis technique uses logistic regression. The results of the research that has been done show that the variables of profitability and company growth have a negative influence on going concern audit opinions. While the solvency variable is able to moderate the negative effect of profitability and company growth on going concern audit opinions, The results of this study are one of the objectives of providing information to auditors so that they can pay attention to the various aspects studied in providing a sustainable audit.